Evaluasi Kondisi Kerusakan Permukaan Jalan Dengan Menggunakan Metode Pavement Condition Index ( PCI) ( Studi Kasus : Jalan Riau Ujung Pekanbaru ) - Melinda, Hapni; Sebayang, Mardani; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Road is one of the land transportation infrastructures which is very important for users of land transportation modes. If this infrastructure functions properly, it will affect the economic growth of the community because it facilitates population mobility, and increases other social activities. Damage to the road will interfere with driving comfort and safety, such as in Jalan Riau Ujung in Pekanbaru City, where the pavement has suffered a lot of damage such as potholes, transverse cracks and abrasion. The purpose of this study is to identify the type of damage, classify the type of damage and determine the level of pavement damage, and to determine the priority of handling road damage. This research was conducted visually with the Pavement Condition Index (PCI) method. The Riau Ujung Pekanbaru road segment with a length of 1.8 km and a width of 7 m is divided into several segments, each segment is evaluated by measuring dimensions, identification of the type and degree of damage to obtain a PCI value. The results of the analysis showed that damage occurred, among others, Elongated Cracks, Removal of Grains, Holes, Lumps, Puffs, Cracked Edges, Cracked Crocodile Skins, Patches and Cracked Blocks. The average PCI value for the Riau Ujung road in Pekanbaru City is 75.51 categorized in Very Good condition, so that the handling of road damage as referred to in the collector road classification is 6-10 years of maintenance. Keywords: PCI, Pavement Condition Index, Level of Road Damage